Value education in Qur'anic learning based on Sab’atu Al-Ahrāf - Sinwan, Husaini Bin; Zamsiswaya, (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
Sab'atu Al-Ahrāf is a concept of teaching the Qur'an with differences in seven Arabic variations in pronunciation. This concept has been known since the time of the Prophet Muhammad. This difference in qiraat makes the Qur'an so rich in wisdom values, both in a cultural perspective and in a religious perspective. This study aims to integrate value education with Sab'atu Al-Ahrāf-based Qur'an learning. The research method used is a qualitative method, and the type of research is library research that uses a descriptive analysis approach. The results showed that there are three value educations that can be integrated with Sab'atu Al-Ahrāf-based Qur'anic learning, namely moral education, religious education, and socio-cultural education. Moral education includes moral education, character education, ethics education, and value education; religious education includes education about sharia, tawhid, tasawwuf, and tawhid; and socio-cultural education includes education about human relations in the socio-culture of a society. Integralization of the three educations can create a comprehensive understanding and knowledge of the Qur'an and the values associated with it. Abstrak Sab’atu Al-Ahrāf merupakan konsep pengajaran al-Qur’an dengan perbedaan tujuh variasi bahasa Arab dalam pengucapannya. Konsep ini sudah dikenal sejak masa Rasulullah SAW. Perbedaan qiraat ini menjadikan al-Qur’an begitu kaya dengan nilai-nilai kearifan, baik dalam perspektif budaya maupun dalam perspektif agama. Penelitian ini bertujuan untuk mengintegrasikan pendidikan nilai dengan pembelajaran al-Qur’an berbasis Sab’atu Al-Ahrāf. Metode penelitian yang digunakan adalah metode kualitatif dengan jenis penelitiannya adalah penelitian pustakayang menggunakan pendekatan deskriptif analisis. Hasil penelitian memperlihatkan bahwa ada tiga pendidikan nilai yang bisa diintegrasikan dengan pembelajaran al-Qur’an berbasis Sab’atu Al-Ahrāf, yaitu pendidikan moral, pendidikan keagamaan, dan pendidikan sosial budaya. Pendidikan moral meliputi meliputi pendidikan akhlak, pendidikan karakter, pendidikan etika, dan pendidikan nilai; Pendidikan keagamaan meliputi pendidikan tentang syariat, tauhid, tasawwuf, dan tawhid; dan Pendidikan sosial budaya meliputi pendidikan tentang hubungan antar manusia dalam sosial budaya sebuah masyarakat. Integralisasi ketiga pendidikan tersebut dapat menciptakan pemahaman dan pengetahuan yang komprehensif tentang Al-Qur’an dan nilai-nilai yang terkait dengannya.